Linking farmers with markets - Bolivia and Peru. Implementation of farmer business school to improve small-scale farmer access to markets. Project profile - International Potato Center (International Potato Center, 2019)
Rural communities in Bolivia and Peru rely heavily on potato for their food security and livelihoods. This project fights rural poverty by helping male and female farmers become profitable potato business managers with enhanced resilience to climate variability and change.